Development of insect repellent finish by a simple coacervation microencapsulation technique. Issue 2 (26th March 2018) - Sharma, Rachna; Goel, Alka
Abstract : Purpose: The paper focused onto the development of microcapsules by using two essential oils. It proposes the uses of eucalyptus oil and cedarwood oil as a natural insecticide. The purpose of this paper is to demonstrate the application of developed microcapsules to impart insect repellency on textile substrate. Design/methodology/approach: The paper opted for an experimental study using two essential oils and gum in formations of microcapsules through a simple coaseravtion encapsulation technique. The developed solution was analyzed, including confirmation of size and structure through. Application of developed finish on substrate was also undertaken to prove better ability as repellent fabric. Findings: The paper highlights useful invention of microencapsulated fabric developed with the combination of gum acacia and eucalyptus oil as core and shell material. The developed fabric has better ability to repel silverfish as compared to microencapsulated fabric developed with gum acacia (shell) and cedarwood oil (core). Research limitations/implications: Due to the lack of time and less availability of essential oils, only two oils were used to test the insect repellent behavior. Practical implications: This paper fulfills an identified need, it includes implications for the development of a very useful natural insecticide to repel silverfish ( Lepisma saccharina ) insect. This insect is a very common problem found in cloth wardrobes and bookshelves; it mainly attacks the fabric with cellulosic content and starch. Social implications: Society will get major benefit of using these microencapsulated finished fabrics, which repel silverfish from their home and keep their clothing and books safe for longer period. The natural fragrance and medicinal benefits of these essential oils can never be ignored. Originality/value: This study sets a new approach to repel insects like silverfish from the bookshelves and clothing wardrobes. A layer of insect repellent microencapsulated finished fabric can be added in these shelves and wardrobes. It is an eco-friendly approach of using natural essential oils instead of chemical insecticides.